D.Z. Phillips' contemplative philosophy of religion : questions and responses - Sanders, Andy F. (Ashgate, 2007)
This collection presents a critical discussion and exploration of the late D.Z. Phillips' contemplative approach in the philosophy of religion. It offers a major contribution to the development of alternative approaches in the philosophy of religion, and presents D.Z. Phillips' last reflections on eternal life, petitionary prayer and radical pluralism.